OPTIMIZATION OF THE OPERATIONAL CHARACTERISTICS OF STRUCTURAL ELEMENTS OF AIRCRAFT MADE OF BASALT PLASTIC - Юніс, Б.Н.; Мірошніков, В.Ю. (SWorldJournal, 2025)
The modern aerospace industry demands materials that not only enhance the performance and technological capabilities of aerospace structures but also reduce operational, maintenance, and disposal costs. Polymer composite materials (PCMs) have emerged as